2023
DOI: 10.1002/adma.202208740
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Porous Conductive Substrates for Gas‐Phase Photoelectrochemical Hydrogen Production

Abstract: Gas diffusion electrodes are essential components of common fuel and electrolysis cells but are typically made from graphitic carbon or metallic materials, which do not allow light transmittance and thus limit the development of gas‐phase based photoelectrochemical devices. Herein, the simple and scalable preparation of F‐doped SnO2 (FTO) coated SiO2 interconnected fiber felt substrates is reported. Using 2–5 µm diameter fibers at a loading of 4 mg cm−2, the resulting substrates have porosity of 90%, roughness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…[5,6] Several porous photoanodes (ntype TiO 2 , WO 3 , BiVO 4 , Fe 2 O 3 , and SrTiO 3 ) and photocathodes (ptype CuInS 2 and Cu 2 O) have been prepared on porous felt substrates composed of carbon and titanium microfibers. [4][5][6][7][8][9][10][11][12][13] Carbon microfibers could be oxidatively decomposed during thermal treatments and photoanodic reactions. In contrast, titanium microfibers have better tolerance under oxidative conditions compared with carbon microfibers.…”
Section: Microfiber-felt Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…[5,6] Several porous photoanodes (ntype TiO 2 , WO 3 , BiVO 4 , Fe 2 O 3 , and SrTiO 3 ) and photocathodes (ptype CuInS 2 and Cu 2 O) have been prepared on porous felt substrates composed of carbon and titanium microfibers. [4][5][6][7][8][9][10][11][12][13] Carbon microfibers could be oxidatively decomposed during thermal treatments and photoanodic reactions. In contrast, titanium microfibers have better tolerance under oxidative conditions compared with carbon microfibers.…”
Section: Microfiber-felt Substratesmentioning
confidence: 99%
“…[6] (C) Photographic and SEM images of FTO-coated transparent porous conductive substrates (TPCS). [13] (D) Photographic and SEM image of a bulk-heterojunction (BHJ)/CuSCN/TPCS photocathode and its PEC response toward Eu 3 + reduction (pH 2) under 1-sun simulated illumination (AM1.5G, 100 mW cm À 2 ). Adapted from Ref.…”
Section: Cu 2 O On Feltmentioning
confidence: 99%
“…Prototype gas-fed PEC systems have been developed using a proton exchange membrane (PEM) with a porous photoanode and cathode electrocatalyst. 7–23 We found that the surface coating of the porous photoelectrodes with perfluorinated sulfonic acid (PFSA) ionomers significantly enhanced the PEC performance of the vapour-fed system operating without liquid electrolyte. 13–17 The surface ionomer decorated on the porous photoanodes forms a triple-phase boundary, allowing gas, semiconductor particles, and electrolyte to come into contact simultaneously, facilitating proton-coupled electron transfer (PCET) and charge transport in the gas-fed PEC cell.…”
Section: Introductionmentioning
confidence: 99%
“…2 Based on the design of polymer electrolyte membrane (PEM) electrolyzers, gas-phase PEM-PEC cells have recently emerged as a scalable design for green hydrogen production. 3 This device improves ion conductivity and allows the creation of higher surface area photoelectrodes. 4,5…”
Section: Introductionmentioning
confidence: 99%